2017
DOI: 10.5588/ijtld.16.0658
|View full text |Cite
|
Sign up to set email alerts
|

Migration histories of multidrug-resistant tuberculosis patients from the Thailand-Myanmar border, 2012–2014

Abstract: Our results show that at least some migrant workers in the region carry MDR-TB, and indicate that this subgroup of the population is important with regard to the transmission of MDR-TB throughout the region. Migrants in this region come into contact with high numbers of people and may be able to spread the disease across wide geographic ranges. Access to diagnosis and treatment and socio-economic development are at least as important as any TB control measures, meaning that innovative and bold approaches that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Our study brings in-depth understanding of fever conception and its believed causes, and identi es determinants associated with health-seeking behaviour amongst migrants from the Thai-Myanmar border where the burden of fever is high [5][6][7][8][9][10][11][12] . The only comparable study in the region was carried out in the early 2000s, whereas the economic context has dramatically changed since then, with a USD15 billion China-Thailand-Myanmar Special Economic Zone, and over USD25 billion-a-year gaming industry constructed on the Myanmar side of the border since 2019 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study brings in-depth understanding of fever conception and its believed causes, and identi es determinants associated with health-seeking behaviour amongst migrants from the Thai-Myanmar border where the burden of fever is high [5][6][7][8][9][10][11][12] . The only comparable study in the region was carried out in the early 2000s, whereas the economic context has dramatically changed since then, with a USD15 billion China-Thailand-Myanmar Special Economic Zone, and over USD25 billion-a-year gaming industry constructed on the Myanmar side of the border since 2019 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In rural northern Thailand, a public health campaign aiming to limit antibiotic use was followed by a drastic reduction of general medicine availability in informal shops, pressurising villagers to seek health in hospital, 9-10 kilometres away from their village, even for mild symptoms such as headache 51 . Ignoring the language terminology and population beliefs may, therefore, worsen symptom identi cation and response, while being irrelevant to alleviate the burden of both febrile illness and AMR in Southeast Asia [5][6][7][8]54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional economic difference is an important driving force for population mobility [5,10]. Existing research indicated that in areas with poor economic conditions, there is a high TB risk [11,12], and TB transmission has been con rmed to be associated with migration [13].…”
Section: Introductionmentioning
confidence: 99%
“…O uso de drogas pode fazer com que os medicamentos do tratamento da TB não sejam tomados com a regularidade necessária, aumentando o risco de resistência microbiológica e também favorecendo o abandono do tratamento, variáveis que não foram associadas aos imigrantes nessa pesquisa.A cultura de escarro é o método padrão ouro de diagnóstico da TB114 . Além disso, a associação positiva encontrada entre imigrantes e o resultado positivo desse teste pode estar relacionada ao fato de diversas pesquisas sugerirem maior número de casos de MDR-TB entre imigrantes do que entre a população autóctone[125][126] . O TRM-TB também é o teste mais indicado para o diagnóstico de TB em populações vulneráveis127 .…”
unclassified